Farkhanda Lodhi's Unpublished, Unedited Punjabi Interview - Latif, Wasif (Makhz (Research Journal), 2024)
This article deals with the unedited and unpublished interview of prominent Punjabi/Urdu writer Farkhanda Lodhi made by Ms. Rabia Ghias student of Dr. Muhammad Abbas Najmi in GC University, Lahore in 2008. The student was assigned to interview Farkhanda Lodhi as an assignment by her teacher keeping in mind the literary status of Mrs. Farkhanda Lodhi. This interview is presenting as it is in Punjabi, so that an historical document may be preserved. This interview reveals many important aspects which are of great importance for researcher. It is necessary to mention that both Mrs. Farkhanda Lodhi and Dr. Abbas Najmi are not alive.